Monitoring dan Kontrol Kualitas Air Kolam Ikan Menggunakan IoT di Pondok Pesantren Harakatul Qur'an Kota Padang - Darwison Daud (Jurnal Andalas: Rekayasa dan Penerapan Teknologi, 2025)
The management of fish pond water quality at Pondok Pesantren Harakatul Qur'an is still conducted manually, leading to potential fish mortality due to suboptimal water conditions. To address this issue, this community service project developed an Internet of Things (IoT)-based monitoring and control system accessible via smartphones. The system is designed to regulate water quality parameters such as pH, temperature, and turbidity while optimizing the use of solar cells installed on-site. The implementation includes installing water sensors, automating water pump control, and integrating real-time data into an IoT application. The results show improved efficiency in water management, better water condition stability, and increased fish productivity. Additionally, renewable energy from solar cells is utilized more efficiently with an advanced monitoring system. With this system, partners can independently manage and control water quality, enhancing the sustainability of fish farming. This project also provides educational benefits for students in applying IoT-based technology for more efficient and environmentally friendly water resource management.